Stranded assets and subcritical coal: The risk to companies and investors - Caldecott, B; Dericks, G; Mitchell, J (Smith School of Enterprise and the Environment, 2015)
We have located subcritical coal-fired power stations globally and identified the ones most at risk of stranding due to their carbon intensity and deleterious effects on local air pollution and water stress. The research shows which companies own these assets and ranks companies by exposure. Furthermore, we examine how environment-related risks facing subcritical coal assets might develop in the future.